Model Rekonstruksi Arsip Berbasis Teknologi Informasi untuk Mendukung Transparansi dan Akuntabilitas Publik - Dewi, Syanti (Indo Publishing, 2025)
Archival management is a crucial element in establishing transparent and accountable governance. However, archival practices in Indonesia still encounter several obstacles, including the dominance of manual records, limited technological infrastructure, fragmented systems, and low digital literacy among civil servants. These conditions make archives difficult to access, prone to loss, and less supportive of public information disclosure. This study aims to formulate an information technology-based archival reconstruction model that addresses these issues while strengthening bureaucratic accountability. The research employed a descriptive qualitative approach, with data collected through literature review, observation, and semi-structured interviews with archivists and public information officers (PPID). Data analysis was conducted thematically, with triangulation applied to ensure validity. The findings indicate that the proposed archival reconstruction model consists of three main components: (1) process, which includes digitization, classification, metadata, and audit trail mechanisms; (2) technology, represented by a web-based electronic records management system equipped with security, encryption, backup, and inter-agency integration features; and (3) openness, achieved through public archival portals that allow citizen participation while maintaining data protection. The model offers advantages in terms of efficiency, transparency, and accountability, yet faces challenges related to infrastructure, human resources, and policy consistency. The study recommends the adoption of national archival standards, capacity building for human resources, investment in IT infrastructure, and phased implementation to ensure system sustainability. These findings are expected to serve as a reference for public institutions in developing digital archival governance that is more transparent, accountable, and responsive to public needs.